Order Ideals on Lexicographic Direct Sum of Three Totally Ordered Abelian Groups - Latifah, Dian; Gozali, Sumanang Muhtar; Rosjanuardi, Rizky; Albania, Imam Nugraha (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Order ideals play an important role in the study of abstract algebra, especially in the study of ordered groups. In this paper, we focus on the study of order ideals in lexicographic direct sums of totally ordered Abelian groups. We begin by examining the order ideals in the group of integers , and the group of real numbers It is shown that there are no non-trivial order ideals in both groups. Next, we revisit the order ideals in the lexicographic direct sum of two totally ordered Abelian groups, The only non-trivial order ideal of is Furthermore, our study extends to the lexicographic direct sum of three totally ordered Abelian groups: and We investigate the non-trivial order ideals in these structures. It is stated that the non-trivial order ideals of are only and Furthermore, the non-trivial order ideals of are only and .Keywords: order ideal; lexicographic order; direct sum.